Motivations for providing CSR-mediated initiatives in mining communities of Ghana: A multiple-case study - Richard Kwasi Boso; Sam K. Afrane; Daniel K. Inkoom (International Journal of Corporate Social Responsibility (JCSR), 2017)
This study used an eclectic multiple-case design to explore what drives three large-scale mining companies' involvement in CSR-mediated development activities, and their philosophical underpinning. The research discovered that although there were nuances between cases in the order in which they rated the strength of 11 potential drivers of CSR, eight of them were important. Three (3) of these were strong drivers - reputation management, pre-emptive anti-regulationism, and pre-existence of local development plans. Five others were moderately strong drivers. The investigations further found that the philosophical underpinnings of the case companies' CSR were based on 'Common-Sense Morality,' a duty-based deontological moral philosophy that is a departure from widely held instrumental positions associated with Egoism. It also identified constrained profit-maximization as the CSR strategy from which their CSR policies emanated.
Keywords: 650; Corporate Social Responsibility; Drivers of CSR; Gold mining; Ethical philosophy; Community development; Gold Fields Ghana; AngloGold Ashanti; Newmont Ghana Gold